Desempenho de controladores aplicados a grupo motogerador operando com biogás de águas residuárias - Diniz, Pedro Henrique Santiago (2020)
The improvement of Renewable Energy Resources (RERs) based power plants is a real and modern global challenge, therefore, biogas applied in reciprocating Internal Combustion Engines (ICE) is a good alternative to this challenging task. Biogas can be obtained from various sources and its composition varies according to the biomass type used in its production, but the majority of this fuel is composed of methane (CH4) and carbon dioxide(CO2). This composition variation implies a change in the Lower Heating Value (LHV), it affects the use of biogas in energy generation systems. However, although this fuel is a good alternative, it is difficult to find in the market a reliable control to hold the power quality following National Energy Agency Electrical (ANEEL) requirements. In such a context, this dissertation presents a four control schemes to assure the power quality by a generator set operating with biogas from wastewater treatment. For this, a mathematical model was developed to represent the mechanical and electrical phenomena involved in the generation process. This model is linearized by expanding the Taylor series in order to optimize the parameters of the Proportional, Integral and Derivative (PIDs) controllers used in all control schemes studied. Two methods for PID tuning are used: the tune from Simulink environment in MATLAB; the Particle Swarm Optimization (PSO). The performance of each control system is evaluated under three simulation scenarios: load variation; biogas composition variation; load and biogas composition variation simultaneously. The tests in Simulink/MATLAB show that the best control scheme is the titled TWO-PIDS, it is composed by two PID controllers optimized by PSO and they operate in parallel and they are switched by a Fuzzy Logic controller. TWO-PIDS enables the power plant remain connected to the grid in all three simulation scenarios, because power frequency and voltage remained within limits imposed by ANEEL.